Users, Vehicles Electrics, and Energy Markets in Colombia - Betancur-Ramos, Alejandro; Grimaldo-Guerrero, John; Grimaldo-Guerrero, John William; Rivera-Alvarado, Juan; Gómez-Mesino, Eilin (International Journal of Energy Economics and Policy, 2022)
The Colombian government approved Law 1964 of 2019, which is expected to favor the massification of electric vehicle technologies. Since 2010, this technological migration has begun, which has not managed to have a substantial impact on the automotive sector. The research reviewed the industry’s regulatory framework and identified variables that impact the market. Through the MICMAC methodology, they are evaluated to establish the key variables that can influence the other variables. The results obtained identify that the price of electricity and the lack of knowledge or business models are critical elements in improving the development of the electric vehicle sector. These results indicate that it is necessary to propose methodological changes to decrease the price of electricity and promote the development of business models so that users take an active role in the market.